The Ternary System H3PO4-Ca(OH)2-H2O Isotherms at 15 and 45 °C - Labgairi, K.; Jourani, A.; Kaddami, M. (Journal of Applied Solution Chemistry and Modeling, 2016)
The solid–iquid phase equilibria of the system H3PO4–Ca(OH)2–H2O were studied under air pressure using a synthetic method based on conductivity measurements. Two isotherms at 15 and 45 °C were completely defined. The stable solid phases which appear in this range of temperature are hydroxyapatite (Ca10(PO4)6(OH)2), calcium hydrogen phosphate dihydrate (CaHPO4.2H2O), calcium hydrogen phosphate anhydrous (CaHPO4) and calcium dihydrogen phosphate monohydrate (Ca(H2PO4)2.H2O). These solid phases were characterized using X ray diffraction.